2022
DOI: 10.1136/emermed-2021-211524
|View full text |Cite
|
Sign up to set email alerts
|

Performance of early warning and risk stratification scores versus clinical judgement in the acute setting: a systematic review

Abstract: ObjectiveRisk stratification is increasingly based on Early Warning Score (EWS)-based models, instead of clinical judgement. However, it is unknown how risk-stratification models and EWS perform as compared with the clinical judgement of treating acute healthcare providers. Therefore, we performed a systematic review of all available literature evaluating clinical judgement of healthcare providers to the use of risk-stratification models in predicting patients’ clinical outcome.MethodsStudies comparing clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Previous literature reviews have found that clinical decision rules and risk scores rarely outperform clinician gestalt diagnostically or in predicting outcomes 34. Our study supports this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Previous literature reviews have found that clinical decision rules and risk scores rarely outperform clinician gestalt diagnostically or in predicting outcomes 34. Our study supports this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Previous qualitative research has demonstrated that prehospital triage making is often heuristic with triage tools used less commonly as experience increases [ 26 ]. It is perhaps not surprising that subjective real-life decisions outperformed objective triage tool accuracy, as clinical judgement has been consistently demonstrated to be superior in multiple studies across many disease areas [ 27 , 28 ]. This has important implications, as to benefit from better overall triage performance achieved through subjective clinical judgement, some incorrect individual clinical decisions will need to be accepted; and clinical governance strategies to increase triage tool use and adherence may be counterproductive.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating relative systolic change into a NEWS2 model marginally improved predictive performance for 30-day mortality. This yielded the best-performing AUC in this study, which at only 0.74 prompts for consideration on the limitations of risk stratification scores compared with ED clinician judgement, especially when applied to older people living with frailty [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 99%